Sistem Pendukung Keputusan Pemilihan Subkontrak Menggunakan Metode Entropy dan TOPSIS - Jamila Jamila; Sri Hartati (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
Abstract— Outsourcing is a part of production process of manufacturing industry which contribute for suitainability of a manufacture process. Choosing appropriate subcontractor which match spesification is not easy. In order to help company in determining credible subcontractors is needed a decision support system.Selection of decision support system for the production of subcontracting gloves uses Entropy and TOPSIS methods. Entropy method is used to give weight to the criteria. TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method is used to select the best subcontractors, where subcontracting was elected not only has the shortest distance from the positive ideal solution but it also has the longest distance from the negative ideal solution. Designing of systems use ERD and DFD for identifying the needs of users and systems, and as for guiding the software implementation. The results of this research are the establishment of an application used to select subcontractors based on established criteria. Test results on the application can provide decision input/suggestion, although the criteria used in making decision is different. Subcontract selection decision support system can be an alternative to choose subcontractors for the production of gloves in PT. Adi Satria Abadi Yogyakarta.Keywords— DSS, Decision Support System, Entropy, TOPSIS, Subcontract